2007
DOI: 10.1242/jeb.02752
|View full text |Cite
|
Sign up to set email alerts
|

The effect of decoupling olfactory and visual stimuli on the foraging behavior ofManduca sexta

Abstract: SUMMARY Within an appetitive context, Manduca sexta, a nectivorous nocturnal hawkmoth, can be attracted by a range of stimuli including floral volatiles and visual display, carbon dioxide and water vapor. Several studies on this and other flower-visiting insects have shown how olfactory and visual stimulation play (or do not play) a role in attraction and feeding. Nevertheless, these studies have consistently manipulated stimuli in a`presence–absence' manner. Here, we experimentally decoupled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 37 publications
6
127
1
Order By: Relevance
“…On the other hand, M. sexta has consistently shown more significant responses to visual targets when olfactory stimuli were also provided (Raguso & Willis 2002;Goyret et al 2007;Riffell et al 2008). Here, the combined results from our behavioural experiments and spectroradiometric measurements support the hypothesis that naive M. sexta has difficulty recognizing an odourless visual target as a nectar source when their vision is impaired by suboptimal b-carotene intake during their larval stages.…”
Section: Discussion (A) B-carotene and Foraging Behavioursupporting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, M. sexta has consistently shown more significant responses to visual targets when olfactory stimuli were also provided (Raguso & Willis 2002;Goyret et al 2007;Riffell et al 2008). Here, the combined results from our behavioural experiments and spectroradiometric measurements support the hypothesis that naive M. sexta has difficulty recognizing an odourless visual target as a nectar source when their vision is impaired by suboptimal b-carotene intake during their larval stages.…”
Section: Discussion (A) B-carotene and Foraging Behavioursupporting
confidence: 77%
“…Our previous studies using naive M. sexta (reared on standard diet) showed that floral odours can elicit both upwind odour plume tracking and visually guided flower searching (Goyret et al 2007). When olfactory stimulation was spatially or temporally decoupled from the visual target (i.e.…”
Section: Discussion (A) B-carotene and Foraging Behaviourmentioning
confidence: 99%
“…3). For these hawkmoths, responses to floral CO 2 clearly depend on the sex of the moth and the conditions under which it perceives this stimulus; non-host-plant floral odors attract both sexes of M. sexta in the absence of CO 2 (44). The contextdependent responses of female moths to the combined stimulus of host-plant odor and CO 2 are conflated with nonappetitive behaviors likely to be associated with oviposition, as discussed above.…”
Section: Context Dependence Of Female Responses In Binary-choice Assaysmentioning
confidence: 87%
“…(42,43) and floral approach is elicited by olfactory and/or visual stimuli (43) that are most effective when combined (44), after which probing is guided by visual and tactile inputs (7). Upon closer inspection, these behavioral ''rules'' are somewhat flexible, depending on the spatial and temporal scale (44) and the context in which specific stimuli are perceived [e.g., after appetitive conditioning (45,46)]. With this framework in mind, we explored how CO 2 might interact with other floral stimuli in behavioral assays with M. sexta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation